La planta ideal de yuca para obtener rendimientos máximos - Cock, James H.; Franklin, D.; Sandoval, G; Juri, P. (International Center for Tropical Agriculture, 1979)
A series of trials were carried out using cassava. Crop growth rate increased with leaf area up to LAI 4; root growth rate increased up to LAI 3-3.5, then declined. LAI is determined by leaf size, leaf formation rate and individual leaf life. Leaf size reached a max 4 mo after planting and then decreased; the max was a varietal character. Leaf life was reduced by shading but in full daylight was determined by the var. Leaf formation rate/shoot apex showed little genetic vafiation and declined with time; large differences in leaf formation rate/plant were determined by differences in branching pattern. Top growth had preference over root growth, and root sink was not limiting when root no./plant was equal to or greater than 9. A computer program was written to implement a dynamic growth model, which suggests that high-yielding plants will branch late in life and possess large leaves and long leaf life. Potential yields of greater than 25 t/ha/yr dry roots are obtainable at 400-500 g cal (cm)-2 day radiation. (AS)